2019
DOI: 10.1093/jipm/pmz002
|View full text |Cite
|
Sign up to set email alerts
|

Human and Technical Dimensions of Potato Integrated Pest Management Using Farmer Field Schools: International Potato Center and Partners’ Experience With Potato Late Blight Management

Abstract: In the 1990s, the integrated pest management (IPM) team for potato late blight (IPM-late blight) at the International Potato Center (CIP) began to address the management of this complex potato disease by combining crop protection with social and behavioral sciences. Since the early 2000s, the team has worked with research and development organizations in countries in Asia, sub-Saharan Africa, and South America to develop farmer discovery-based learning methods using farmer field schools (FFS). The principles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
6
10
0
Order By: Relevance
“…This finding aligns with other studies that indicate that experiential learning improved the problem-solving capacity of farmers for integrated pest management in farmer field schools in Africa (Davis et al 2012;Ortiz et al 2019). Similar findings were also reported improvement of farmers' knowledge, perceptions, and practices in pest management in South America and Asia (Feder et al 2003;Ortiz et al 2019). Moreover, the importance of hands-on practical learning based on experiential learning principles has been reported earlier to improve the decision-making capacity of smallholder farmers in a complex farming system (Gallagher 2003;Ortiz et al 2019).…”
Section: The Influence Of Experiential Learning On Farmers' Knowledgesupporting
confidence: 92%
See 4 more Smart Citations
“…This finding aligns with other studies that indicate that experiential learning improved the problem-solving capacity of farmers for integrated pest management in farmer field schools in Africa (Davis et al 2012;Ortiz et al 2019). Similar findings were also reported improvement of farmers' knowledge, perceptions, and practices in pest management in South America and Asia (Feder et al 2003;Ortiz et al 2019). Moreover, the importance of hands-on practical learning based on experiential learning principles has been reported earlier to improve the decision-making capacity of smallholder farmers in a complex farming system (Gallagher 2003;Ortiz et al 2019).…”
Section: The Influence Of Experiential Learning On Farmers' Knowledgesupporting
confidence: 92%
“…The study indicated that none of the farmers knew to recognize the causes of the disease and most did not identify any other control methods apart from roguing. This finding aligns with other studies that indicate that experiential learning improved the problem-solving capacity of farmers for integrated pest management in farmer field schools in Africa (Davis et al 2012;Ortiz et al 2019). Similar findings were also reported improvement of farmers' knowledge, perceptions, and practices in pest management in South America and Asia (Feder et al 2003;Ortiz et al 2019).…”
Section: The Influence Of Experiential Learning On Farmers' Knowledgesupporting
confidence: 91%
See 3 more Smart Citations